Structural Characterization of the Hot-rolled Ti-25Ta-xZr Alloys by Rietveld Method - Kuroda, Pedro Akira Bazaglia; Grandini, Carlos Roberto [UNESP]; Afonso, Conrado Ramos Moreira (FapUNIFESP (SciELO), 2023)
This paper aims to analyze the structure of the Ti-25Ta-xZr system alloys (x = 0, 10, 20, 30, and 40% wt.) after melting and hot-rolling by Rietveld’s technique. The results confirm that zirconium acts as a β phase stabilizer (in which the Ti-25Ta-40Zr alloy is fully β in the as-cast condition), increases the lattice parameters of the phases, decreases the c/a ratio of the α phase, consequently, decreases the elastic modulus values (86 to 72GPa) and decreases the atomic packing factor (APF) of the alloys (60% reduction compared to alloys with and without zirconium in the as-cast condition and 50% reduction in the hot-rolled condition). Concerning hot-rolling, this mechanical process induces the α phase formation and increases the atomic packing factor of the alloys (APF). By the William-Hall technique, it was possible to calculate the average crystalline size and the micro-strain of the structures.
Keywords: Rietveld; Structural charactarization; Ti-25Ta-xZr